TRANSFORMASI DIGITAL DALAM MANAJEMEN KEUANGAN: TINJAUAN LITERATUR TERSTRUKTUR TERHADAP PERAN FINTECH DALAM EFISIENSI DAN INKLUSI KEUANGAN - Nauli, Kembang; Nauli, Harum; Ansella Thalita Hulu, Ruth; Munthe, Kornel; Silalahi, Donalson (Penerbit Lafadz Jaya, 2025)
The development of fintech has revolutionized financial management by driving operational efficiency and expanding financial inclusion in various regions. This article presents a structured literature review using the SCISCAPE method to analyze the role of fintech in the digital transformation of financial management. The study identifies positive trends in fintech adoption and its contribution to increasing access to financial services, but also reveals significant challenges such as low digital literacy, inadequate regulation, and data security risks. In addition, this article underlines the need for further research that focuses on fintech sustainability, ESG principle integration, and its social impact. The SCISCAPE approach has proven effective in providing a comprehensive and critical overview of fintech research developments, while opening new directions for future studies. These findings are expected to be a reference for researchers, practitioners, and policymakers in developing an inclusive, safe, and sustainable fintech ecosystem.